Implementasi Algoritma K-Means pada Kesiapan Guru Menyelenggarakan Pembelajaran Daring - Eka Budhi Santosa (IKIP PGRI Bojonegoro, 2022)
Abstract: Teachers need certain characteristics to be ready to organize online learning. The purpose of this research is to see the readiness of teachers in conducting online learning. The characteristics of the teachers collected were gender, generational, last education, teacher tenure, teacher's internet self-efficacy level, learning environment and variations of online learning models. This study uses the K-Means algorithm for clustering, then the analysis of the relationship between variables is used by Spearman's rho. The K-Means algorithm was performed on a dataset of 285 teachers. The results of the K-Means analysis obtained 8 clusters with various characteristics of each cluster. Furthermore, the Spearmans Rho Correlation analysis obtained significant correlation results with probability values > 0.05 being